Topical Corticosteroids Misuse: A Burning Issue - Neupane, Saraswoti (Nepal Journal of Dermatology, Venereology & Leprology, 2019)
Since the introduction of hydrocortisone into dermatology, a tremendous development has occurred in the field of topical corticosteroids. With the growing use of topical corticosteroids, a serious concern for its misuse is to be highlighted. This matter is of a great concern. Proper guidelines and legislation on the use of topical corticosteroids are warranted to combat this serious issue.